The Boy’s Froissart de Lanier ou la réappropriation d’une mémoire européenne à destination des garçons en Amérique (Perspectives Médiévales)
Why did Sidney Clopton Lanier decide, shortly after the Civil war, to write a book for young male American readers in which he adapted the Chronicles of Froissart, chronicler of the 14th century who had recounted at the time the Hundred Years’ war ? We will try to understand the relationship that Lanier established between Europe and America, and in particular to identify the founding role played by Caxton and Lord Berners thanks to whom Froissart became known to the English. The main purpose of this contribution is to reconstruct the thread or lineage leading from Froissart to Sidney Clopton Lanier, from Europe to the old South, while including two iconic figures of the 15th and 16th centuries in England, Caxton and Lord Berners, who contribute to anchoring the young American reader in the land of prestigious ancestors.